2013
DOI: 10.1080/00015458.2013.11680928
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Hernias in Female Children

Abstract: A sliding hernia is more common in female children under the age of 1 year and surgical treatment should be planned within a short period once the diagnosis is made. In addition, this recent statistical value for subjects aged 0 to 1 year and over 1 year can be used in new clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…The advantage of LH was highlighted in female infants with sliding or incarcerated ovary/ adnexa. Articles have reported that 15 -22.4% of the inguinal hernias in female children are sliding hernias, and that the most frequently sliding organ is the ovary, followed by the Fallopian tubes [16]. Drawbacks associated with the reproductive system are a hidden but not a negligible problem.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of LH was highlighted in female infants with sliding or incarcerated ovary/ adnexa. Articles have reported that 15 -22.4% of the inguinal hernias in female children are sliding hernias, and that the most frequently sliding organ is the ovary, followed by the Fallopian tubes [16]. Drawbacks associated with the reproductive system are a hidden but not a negligible problem.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the ovary is herniated in15%-20% of female patients with inguinal hernia. [5]. Ovarian hernia is more frequently seen in infants than in older girls and early or emergency surgical repair is female recommended because of the risk of ovarian torsion.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian hernia is defi ned as herniation of the ovary into the inguinal hernia sac. It is reported that 15%-20% of all canal of Nuck hernias containing ovaries and on some occasion with its Fallopian tube [5]. In these cases, ovarian torsions have been reported in 2%-33%, emphasizing the importance of early surgical repair in irreducible hernias, even in asymptomatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Мы не встретили в доступной литературе описа-ние наблюдений скользящей бедренной грыжи в детском возрасте [9][10][11][12].…”
Section: Discussionunclassified